Can probiotic supplements improve the symptoms of autism spectrum disorder in children?: A protocol for systematic review and meta analysis. Issue 10 (12th March 2021) - Feng, Kai; Zhao, Ying; Yu, Qingyang; Deng, Jialin; Wu, Jingjing; Liu, Lingjia
Abstract: Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with increasing incidence. The externalizing and internalizing problems among children with ASD often persistent and highly impair functioning of both the child and the family. Children with ASD often develop gut-related comorbidities and dysbiosis can have negative effects on not only the gastrointestinal (GI) tract, but also psychological symptoms. Dietary exclusions and probiotic supplements also have been investigated in the management of ASD symptoms. Especially, there is some anecdotal evidence that probiotics supplements are able to alleviate GI symptoms as well as improve behaviors in children with ASD. Method and analysis: This review will report on overall studies that include randomized control trials, randomized cross-over studies and cluster-randomized trials designs that consider curative effect in children with ASD by probiotic supplements. We will search 6 databases: MEDLINE, Embase, Scopus, PubMed, The Cochrane Library, and Web of Science and we will perform a manual search the journal Autism and information of ongoing or unpublished studies. The Mixed Methods Appraisal Tool (MMAT) will be used to assess quality of articles and the Jadad scale will be used to assess for bias. Assessment of publication bias will be performed using funnel plots generated by Comprehensive Meta-Analysis (CMA) 3.0 software. Clarifying the evidence in this area will be important for future research directions when reformulating and promoting the therapeutic regime in the field. Ethics and dissemination: There are no human participants, data, or tissue being directly studied for the purposes of the review; therefore, ethics approval and consent to participate are not applicable. The results of this study will be presented at conferences and published in peer-reviewed journals. Registration and status: PROSPERO 2019 CRD42019132754.